Farm wages and working conditions in the Albany District, 1957-2008 - Roberts, Tamaryn Jean (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2010)
Agriculture is a major employer of labour in South Africa with about 8.8% of the total labour force directly involved in agricultural production (StatsSA, 2007a). Farm wages and working conditions in the Albany district were researched in 1957 by Roberts (1958) and 1977 by Antrobus (1984). Research in 2008, involving face-to-face interviews of a sample survey of 40 Albany farmers, was undertaken to update the situation facing farm labourers and allowed for comparisons with the work previously done. Farm workers were governed by common law until 1994 when the government intervened with legislation. The introduction of the Basic Conditions of Employment Act (1997) for farm workers, amended in 2002 to include minimum wage legislation, and the Extension of Security of Tenure Act (ESTA) of 1997 impacted the supply and demand of farm workers. Other impacts have been due to the Albany district experiencing an increase in the establishment of Private Game Reserves and game-tourism with a simultaneous decline in conventional farming. It was concluded from the survey conducted that minimum wage legislation decreased the demand for regular and increased the demand for casual labour, which incur lower costs including transaction costs, than their regular counterparts. The ESTA of 1997 contributed to a decreased number of farm residents, which had spin-off affects on the supply of labour. Farmers experienced a simultaneous price-cost squeeze, which furthermore decreased the demand for labour. Studying the working and living conditions showed that farm workers had limited access to educational and recreational facilities which negatively impacted the supply of labour.
Keywords: Agricultural laborers -- South Africa -- Eastern Cape; Agricultural wages -- South Africa -- Eastern Cape; Agricultural laborers -- Legal status, laws, etc. -- South Africa; Agricultural laborers -- Protection -- South Africa; Agricultural laws and legislation -- South Africa; Labour laws and legislation -- South Africa; Labour economics -- South Africa